Editorial of the special edition in English - Nóbriga, Jorge Cássio Costa; Dantas, Sergio Carrazedo (Revista do Instituto GeoGebra Internacional de São Paulo, 2023)
In this special issue we would like this story to be told more explicitly. Of course, it would not be possible to make an issue with all the authors who have already published in the magazine telling their stories with GeoGebra. Thus, we invite authors who, in some way, have representation and recognition within the GeoGebra community in Brazil for the work they have been developing with the software.